2021
DOI: 10.1039/d1cp01565f
|View full text |Cite
|
Sign up to set email alerts
|

C14H10 polycyclic aromatic hydrocarbon formation by acetylene addition to naphthalenyl radicals observed

Abstract: The formation of polycyclic aromatic hydrocarbons (PAHs) during combustion has a substantial impact on environmental pollution and public health. The hydrogen-abstraction-acetylene-addition (HACA) mechanism is expected to be a significant source...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This type of chemistry could eventually lead to the production of dark aerosols (Zhang et al 2013). Recent advances in experimental and theoretical studies of the formation of multi-ringed species (Yang et al 2021) confirmed our earlier speculations, opening up new avenues of investigation for the planets in our solar system and early Earth (Berry et al 2019).…”
Section: Discussionsupporting
confidence: 57%
“…This type of chemistry could eventually lead to the production of dark aerosols (Zhang et al 2013). Recent advances in experimental and theoretical studies of the formation of multi-ringed species (Yang et al 2021) confirmed our earlier speculations, opening up new avenues of investigation for the planets in our solar system and early Earth (Berry et al 2019).…”
Section: Discussionsupporting
confidence: 57%
“…A previous study using a similar molecular beam sampling system at the outlet of a flow reactor also did not detect aryl radicals . We hypothesize that these very reactive aryl radicals may combine with free H-radicals within the residence time of our reactor or abstract H-atoms via a wall reaction at the pinhole of the quartz nozzle . Therefore, the detection of benzene, naphthalene, and phenanthrene instead of phenyl, 1-naphthyl, and 4-phenanthryl in Figure is an artifact of our reactor and sampling system (Supporting Information).…”
Section: Resultsmentioning
confidence: 72%
“…39 We hypothesize that these very reactive aryl radicals may combine with free H-radicals within the residence time of our reactor or abstract H-atoms via a wall reaction at the pinhole of the quartz nozzle. 40 Therefore, the detection of benzene, naphthalene, and phenanthrene instead of phenyl, 1-naphthyl, and 4-phenanthryl in Figure 3 is an artifact of our reactor and sampling system (Supporting Information). Mass peaks m/z = 78, 152, 228, and 229 in Figure 3A are absent in the control experiment (Supporting Information, Figure S11), suggesting that signals at these massto-charge ratios originate from the reaction of 1-naphthyl and phenylacetylene.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The MAE (mean absolute error) and RMSE are reported in kcal mol −1 , and the standard deviations are calculated between the 5 folds for the pre-training set. For the experimental test set, the k rel error is converted to a Gibbs free energy unit (DG ‡ rel or RT(ln k rel )) using eqn (6) to allow easy comparison. The ne-tuned model with no additional feature achieves overall the best performance on unseen reactions for both pre-training and experimental test sets.…”
Section: Comparison Of the Pre-trained And Ne-tuned Modelsmentioning
confidence: 99%